Identificação de Camada Reservatório com Inferência Fuzzy - TEIXEIRA, Mario Junior do Rosário (2022)
This work addresses the problem of transporting geological information obtained from witnessed wells to non-witnessed wells located in the same oil field. The adopted methodology seeks to verify the capacity of a modification of the Mamdani-type fuzzy inference system, with the introduction of changes in the construction of the database and in the defuzzification method to produce the identification of a reservoir layer in an unwitnessed well (a its location and extent along the path of the well). From the creation of the knowledge base produced by the logs registered in a witnessed well, presenting the density profile with low quality. The knowledge base is formed by the sonic profiles (of good quality) and natural gamma ray and by the parameters P and K, which attenuate the effects of the density profile and emphasize the sonic profile. The defuzzification method is changed in order to satisfy the solution of a binary decision problem. This methodology is discussed using synthetic data constructed based on the general sedimentary rock model and real data from three witnessed and drilled wells in the Namorado field, Campos basin. Keywords: geophysics of poço; Fuzzy inference; petroleum geology.